2007
DOI: 10.2298/spat0716080b
|View full text |Cite
|
Sign up to set email alerts
|

The Nisava river water quality as the indicator of the sustainable development of the city of Nis

Abstract: The Nišava river has a great importance for the sustainable development of the city of Niš. From the Mediana spring, which is on the bank of the Nišava, the city of Niš satisfies around 30% of its water demand. The aim of this paper is to, on the basis of the analysis of several tens of parameters of water quality; determine whether the Nišava river is a limiting factor to the sustainable development of the city of Niš. For this purpose the data of Public Utility Company Naissus have been used, as it collects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In the present study, series of daily water temperature (T, o C), electrical conductivity (EC, μS/cm), pH, biochemical oxygen demand (BOD, mg/l), dissolved oxygen (DO, mg/l), total hardness ( o dH), chlorides (Cl -, mg/l), calcium (Ca 2+ , mg/l), magnesium (Mg 2+ , mg/l), nitrate (NO 3 -, mg/l), nitrite (NO 2 -, mg/l) and sulfates (SO The statistic data analysis showed that a large majority of the results of analyses of almost all the water quality parameters is within predicted limits (Brankovic and Trajkovic 2007). There are numerous examples corroborating this assertion.…”
Section: Water Quality Datamentioning
confidence: 99%
“…In the present study, series of daily water temperature (T, o C), electrical conductivity (EC, μS/cm), pH, biochemical oxygen demand (BOD, mg/l), dissolved oxygen (DO, mg/l), total hardness ( o dH), chlorides (Cl -, mg/l), calcium (Ca 2+ , mg/l), magnesium (Mg 2+ , mg/l), nitrate (NO 3 -, mg/l), nitrite (NO 2 -, mg/l) and sulfates (SO The statistic data analysis showed that a large majority of the results of analyses of almost all the water quality parameters is within predicted limits (Brankovic and Trajkovic 2007). There are numerous examples corroborating this assertion.…”
Section: Water Quality Datamentioning
confidence: 99%
“…Public awareness, as well as active participation of the public in the decision making process during development and enforcement of legislation are necessary for sustainable water management (Branković, Trajković, 2007).…”
Section: Role Of Financial Sector For Sustainable Developmentmentioning
confidence: 99%
“…The advantage is that the northeast moderate winds dominate the area thus blocking the higher concentration of exhaust fumes in the air. Nemanjića Boulevard is situated near to Nisava River (Brankovic and Trajkovic 2008), in the eastern part of Niš, in the vicinity of the centre of town and represents a very important traffic route which connects the central to the eastern part of the town. It passes through the town centre parallel with Dr Zorana Đinđića Boulevard and them together flow into Cara Konstantina Boulevard.…”
Section: Human Environment and Exhaust Fumesmentioning
confidence: 99%